Characterization of a vacuum pressure standard based on optical refractometry using nitrogen developed at NIM. (December 2021) - Yang, Yuanchao; Rubin, Tom; Sun, Jianping
Abstract: A vacuum pressure standard called an optical pressure standard (OPS) has been developed at the National Institute of Metrology (NIM) based on optical refractometry using nitrogen gas. The OPS consists of a dual Fabry-Pérot (FP) cavity made from ultra-low expansion glass, a copper chamber housing the FP cavity, a temperature control system, and an optical system. Two tunable diode lasers at a wavelength of 633 nm were frequency-locked to the measurement cavity and the reference cavity, and their frequencies were used to sense the pressure within the copper chamber. The performance of the FP cavity was investigated including the coefficient of thermal expansion and creeping effects. The temperature uniformity assessed for the copper chamber was within 1 mK. The so-called heat-island effect was elucidated and avoided for all measurements performed, and the influence of outgassing and leakage was considered. Non-linear and hysteresis behavior was observed for the deformation of the reference cavity. A direct comparison between the OPS and the NIM primary piston gauge showed no deviations greater than 10 parts per million for the pressures assessed in the range from 20 kPa to 100 kPa. The uncertainty of the OPS was evaluated to be [ ( 0.13 Pa ) 2 + ( 23 · 10 − 6 p ) 2 ] 0.5 ( k = 2 ) . Highlights: Characterization of a refractometry based optical pressure standard. Frequency creeping effects of the Fabry-Pérot cavity. Heat-island effects and outgassing/leakage effects. Pressure comparison against a primary piston gauge from 20 kPa to 100 kPa. Non-linear and hysteresis behavior for the deformation of the reference cavity.